Step-up approach and video assisted retroperitoneal debridement in infected necrotizing pancreatitis: A case complicated by retroperitoneal bleeding and colonic fistula. Issue 3 (September 2015) - Lim, Eugene; Sundaraamoorthy, R.S.; Tan, David; Teh, Hui-Seong; Tan, Tzu-Jen; Cheng, Anton
Abstract: Introduction: Infected Necrotizing Pancreatitis carries a high mortality and necessitates intervention to achieve sepsis control. The surgical strategy for proven infected necrosis has evolved, with abandonment of open necrosectomy to a step-up approach consisting of percutaneous drains and Video-assisted retroperitoneal debridement (VARD). We present a case that underwent VARD complicated by bleeding and colonic perforation and describe its management. Presentation of case: A 38 year-old male with acute pancreatitis developed infected necrotizing pancreatitis. Initial treatment was by percutaneous drainage under radiological guidance and intravenous antibiotics. The infected retroperitoneal necrosis was then debrided using gasless laparoscopy through a mini-incision. Post-operatively, he developed peripancreatic bleeding which was controlled with angioembolisation. He also developed a descending colon fistula which was treated with laparotomy and defunctioning loop ileostomy. He recovered and subsequently had his ileostomy closed twelve months later. The colonic fistula recurred and was treated with endoscopic clips and histoacryl glue injection and finally closed. Discussion: Step-up approach consists of the 3 D's: Delay, drain and debride. VARD is recommended as it is replicable in general surgical units using standard laparoscopic instruments. Bleeding and colon perforation are potential complications which must have multi-disciplinary input, aggressive resuscitation and timely radiologic intervention. Defunctioning ileostomy is recommended to control sepsis in colonic fistulation. Novel fistula closing methods using endoscopic clips and histoacryl glue are potential treatment options. Conclusion: Step-up approach and VARD is the new paradigm to treat necrotizing pancreatitis. Complications of bleeding and colon fistula are uncommon and require multi-disciplinary management. Highlights: Step-up approach consists of the 3 D's: Delay, Drain, Debride. VARD is generalizable in most surgical units using standard laparoscopic equipment. Defunctioning ileostomy diverts faecal stream and controls sepsis in colon fistula. Endoscopic clips and histoacryl glue may help to treat colo-cutaneous fistulas.